(untitled) (Mediscope, 2022)
Background & objectives: Scrub typhus is a mite borne rickettsial illness, caused by the bacterium Orientia tsutsugamushi, which is endemic to Asia pacific region. Due to wide spectrum of non-specific manifestations and inaccessibility of accurate diagnostic tools, it remains underdiagnosed in many countries of Southeast Asia including Bangladesh, resulting in severe life-threatening complications. Therefore, this study was aimed to diagnose scrub typhus through molecular detection of O. tsutsugamushi by ‘Nested Polymerase Chain Reaction (N-PCR)’ among febrile patients in Mymensingh, Bangladesh & to study the socio-demographic as well as clinical characteristics of the diagnosed cases. Methods: It was a cross-sectional type of study, conducted at department of Microbiology, Mymensingh Medical College between March 2018 and February 2019. Blood samples were taken from 453 febrile patients of suspected rickettsial illness, referred from both inpatient and outpatient facility of Department of Medicine and Department of Pediatrics, Mymensingh Medical college Hospital (MMCH). Then DNA was extracted from the whole blood, following Phenol-Chloroform extraction & ethanol precipitation method. Finally, N-PCR was performed on extracted DNA, targeting 47Kda antigen gene, to detect O. tsutsugamushi. Results: Out of 453, this study documented [78 (17.21%)] PCR positive scrub typhus cases, among which majority [42 (53.84%)] were female & maximum [26 (33.33%)] were in age group >15-30 years. Higher number of PCR positive patients [51 (65.39%)] were from rural areas. Among the scrub typhus cases, myalgia (48; 61.53%) was the most common manifestation, followed by headache (44; 56.41%) and cough (44; 56.41%). Eschar was present only in 14 (17.94%) cases and 8 (10.25 %) patients had skin rashes. Leukocytosis and leukopenia were documented in 13 (16.66%) and 5 (6.41%) cases respectively. Decreased Hb% was recorded in 14(17.9%) & 16 (20.5%) cases had thrombocytopenia. Conclusion: This study recorded a high number of scrub typhus cases in Mymensingh region with non-specific febrile manifestations, hindering early & accurate clinical diagnosis. Complications like - renal & hepatic impairment, CNS involvement, ARDS as well as hematological abnormalities were documented also. So, scrub typhus should be considered in the differential diagnosis of undifferentiated febrile illness in Bangladesh. Further molecular studies on scrub typhus might be done throughout the countries to create awareness among physicians & to evaluate actual disease burden. Mediscope 2022;9(1): .30-40